2007
DOI: 10.1051/0004-6361:20066742
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric multi-wavelength (sub)millimeter continuum study of the young high-mass protocluster IRAS 05358+3543

Abstract: Aims. We study the small-scale structure of massive star-forming regions through interferometric observations in several (sub)mm wavelength bands. These observations resolve multiple sources, yield mass and column density estimates, and give information about the density profiles as well as the dust and temperature properties. Methods. We observed the young massive star-forming region IRAS 05358+3543 at high spatial resolution in the continuum emission at 3.1 and 1.2 mm with the Plateau de Bure Interferometer,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
110
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(131 citation statements)
references
References 50 publications
18
110
1
2
Order By: Relevance
“…But only a few studies have been dedicated to the earliest phases of star formation and to regions of 0.1 pc or smaller. In IRAS 05358+3543, Beuther et al (2007) reported the detection of two cores potentially more massive than 8 M with masses of 5−10.5 and 2.7−18.5 M , respectively, inside sizes of the same order as in the present work. One of them can be further subdivided into two objects separated by only 1700 AU, and may contain an B1 star that excites a hyper-compact HII region.…”
Section: Envelope Masses Of the Proto-stellar Objectssupporting
confidence: 79%
“…But only a few studies have been dedicated to the earliest phases of star formation and to regions of 0.1 pc or smaller. In IRAS 05358+3543, Beuther et al (2007) reported the detection of two cores potentially more massive than 8 M with masses of 5−10.5 and 2.7−18.5 M , respectively, inside sizes of the same order as in the present work. One of them can be further subdivided into two objects separated by only 1700 AU, and may contain an B1 star that excites a hyper-compact HII region.…”
Section: Envelope Masses Of the Proto-stellar Objectssupporting
confidence: 79%
“…Alternatively, the presence of winds/outflows (see Sect. 4.2) could mimic a low value of β (Beuther et al 2007). Here we adopt a β = 1.6 in the rest of the paper.…”
Section: Density Temperature and Spectral Indecesmentioning
confidence: 96%
“…The CH 3 OH masers show a linear distribution that was suggested to trace an edge-on disk (PA CH 3 OH ≈ 25 • , Minier et al 2000), which is associated with one of the millimeter continuum sources identified by Beuther et al (2007), i.e. mm1a.…”
Section: S231mentioning
confidence: 97%
“…mm1a. Beuther et al (2007) suggested that mm1a, which is also associated with an hypercompact H ii region and a mid-infrared source, forms a binary system with mm1b (with a projected separation of 1700 AU). Ginsburg et al (2009) observed mm1a with the VLA and they determined a projected separation between mm1a and the CH 3 OH maser site of ∼400 AU suggesting that probably the binary system is formed by mm1a and the massive YSO associated with the CH 3 OH maser site.…”
Section: S231mentioning
confidence: 99%